Inequality and Growth - Roland Jean-Marc Bénabou (Luxembourg Income Study (LIS), 1996)
Using two unifying models and an empirical exercise, this paper presents and extends the main theories linking income distribution and growth, as well as the relevant empirical evidence. The first model integrates the political economy and imperfect capital markets theories while the second is a growth version of the prisoner's dilemma. The economy's growth rate is shown to fall with interest groups' rent-seeking abilities, as well as with the gap between rich and poor. It is not income inequality per se that matters, however, but inequality in the relative distribution of earning and political power.
Keywords: 330